Nutrition Self-Efficacy and Dietary Patterns among Older African American Women in Kansas - Nassim, Grace; Redmond, Michelle; Ofei-Dodoo, Samuel; Benton, Mary; Lu, Kelsey (Kansas Journal of Medicine, 2020)
Introduction. Nutrition is the key contributor to disparities in many chronic diseases. However, little is known about the dietary habits and nutrition self-efficacy beliefs of older African American women with chronic diseases. This study looked at the relationship between nutrition self-efficacy and dietary patterns among older African American women.Methods. A total of 115 African American women 55 years and older, with one or more chronic diseases such as hypertension, diabetes, and hyperlipidemia, were recruited from a midwestern city in Kansas. Participants completed a survey comprised of dietary intake items and the Physical Activity and Nutrition Self-Efficacy (PANSE) scale. Data were analyzed with descriptive statistics, Spearman correlation, and Wilcoxon rank sum test (Mann-Whitney U Test).Results. There was a 79% (91/115) participation rate. Participants were confident in their ability to maintain healthy behaviors (57.67/72; SD = 11.22). The mean dietary score for fats and carbohydrate consumption was 32.67 ± 2.48 compared to 5.89 ± 3.52 for fruit and vegetable intake. A significant positive correlation was observed between fruit and vegetable intake and nutrition self-efficacy. A higher fruit and vegetable intake were observed among married women (mean = 7.35; SD = 4.45).Conclusion. Our findings shed new light on older African American women’s perceptions of healthy eating and the confidence to eat heathy. Based on these results, older African American women met the daily fruit and vegetable recommendations; however, more work is needed to understand how to intervene to improve dietary behaviors regarding fat and carbohydrate consumption in this population. While more research is needed, the findings indicated behavioral theories such as nutrition self-efficacy may have utility in tailoring nutrition interventions in an older African American population.